2002
DOI: 10.1002/kin.10062
|View full text |Cite
|
Sign up to set email alerts
|

Benzylmalonic acid reaction with iodine and behavior in a Briggs–Rauscher oscillator

Abstract: Benzylmalonic acid (BzMA) reacts via an enol mechanism with aqueous iodine to form rather stable iodobenzylmalonic acid. In the presence of iodate, which oxidizes iodide to di‐iodine, the reaction goes to completion. The kinetics of the reaction BzMA + I2 + IO3− + H+ have been studied and the results were interpreted with a suitable mechanism. In a mixture with acidic iodate, hydrogen peroxide, and manganous ions, BzMA can serve as a substrate for a Briggs–Rauscher‐type oscillating reaction. The behavior of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
4
0
1
Order By: Relevance
“…For this reason, the temperature of the reacting mixtures was monitored during all the reactions with a temperature sensor, then an average temperature was calculated. With regard to the noninhibited BR reaction, some studies have shown that the inverse of the oscillatory time (1/d) vs. the temperature T shows an Arrhenius behavior [11] [12]. This result was verified in the present work by using an uninhibited aqueous BR mixture that gave a long duration of oscillations, in order to study the dependence of this parameter on the temperature.…”
Section: Simulations For the Nonoscillating Subsystems Inhibitor Oxisupporting
confidence: 74%
“…For this reason, the temperature of the reacting mixtures was monitored during all the reactions with a temperature sensor, then an average temperature was calculated. With regard to the noninhibited BR reaction, some studies have shown that the inverse of the oscillatory time (1/d) vs. the temperature T shows an Arrhenius behavior [11] [12]. This result was verified in the present work by using an uninhibited aqueous BR mixture that gave a long duration of oscillations, in order to study the dependence of this parameter on the temperature.…”
Section: Simulations For the Nonoscillating Subsystems Inhibitor Oxisupporting
confidence: 74%
“…Activation energies from 60 to 90 kJ mol À1 have been reported for the Briggs-Rauscher reaction with different substrates. [25][26][27] Temperature coefficients from 0.67 to 1.80 were observed in a temperature interval of 10 1C for the oscillatory decomposition of hydrogen peroxide in an acidic aqueous solution in the presence of potassium iodate (Bray reaction). 28 It is important to point out that the apparent activation energy of about 60 kJ mol À1 estimated here under oscillatory conditions is of the same order than that obtained under voltammetric and chronoamperometric conditions.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Growing attention has recently also been dedicated to the production of gas, [12][13][14] to some extent accompanying a vast majority of oscillating reactions, however, with particularly dramatic examples in the family of the BR reaction and its substitutions or additions. 8,[15][16][17] The BR reaction with acetone as the organic substrate has already been considered for its exceptionally well-defined oscillations in the rate of gas production and their practical measurement 18 and effects of the interphase transport of oxygen and iodine on the reaction have been modeled, 19 suggesting a possible interplay of the physical process of gas production and the chemistry of the reaction, which is normally neglected.…”
Section: Introductionmentioning
confidence: 99%
“…The core mechanism of the BR reaction has been considered to be established for the most part since the works of Furrow with Noyes and De Kepper with Epstein, who simultaneously proposed almost identical representations of the reaction, consisting of 11 pseudoelementary steps, as designed in eqs R1−R11 of Table , although its detailed examination remains a fruitful field even today. , Growing attention has recently also been dedicated to the production of gas, to some extent accompanying a vast majority of oscillating reactions, however, with particularly dramatic examples in the family of the BR reaction and its substitutions or additions. , The BR reaction with acetone as the organic substrate has already been considered for its exceptionally well-defined oscillations in the rate of gas production and their practical measurement and effects of the interphase transport of oxygen and iodine on the reaction have been modeled, suggesting a possible interplay of the physical process of gas production and the chemistry of the reaction, which is normally neglected.…”
Section: Introductionmentioning
confidence: 99%